Small-scale flux ropes in ICME sheaths - Ruohotie, J.; Kilpua, E. K. J.; Good, S. W.; Ala-Lahti, M. (Frontiers in Astronomy and Space Sciences, 2022)
Sheath regions of interplanetary coronal mass ejections (ICMEs) are formed when the upstream solar wind is deflected and compressed due to the propagation and expansion of the ICME. Small-scale flux ropes found in the solar wind can thus be swept into ICME-driven sheath regions. They may also be generated locally within the sheaths through a range of processes. This work applies wavelet analysis to obtain the normalized reduced magnetic helicity, normalized cross helicity, and normalized residual energy, and uses them to identify small-scale flux ropes and Alfvén waves in 55 ICME-driven sheath regions observed by the Wind spacecraft in the near-Earth solar wind. Their occurrence is investigated separately for three different frequency ranges between $10^{-2} - 10^{-4}$ Hz. We find that small scale flux ropes are considerably more common in ICME sheaths than in the upstream wind, implying that they are at least to some extent actively generated in the sheath and not just compressed from the upstream wind. Alfvén waves occur more evenly in the upstream wind and in the sheath. This study also reveals that while the highest frequency (smallest scale) flux ropes occur relatively evenly across the sheath, the lower frequency (largest scale) flux ropes peak near the ICME leading edge. This suggests that they could have different physical origins, and that processes near the ICME leading edge are important for generating the larger scale population.